A Systematic Calculus-Based Analytical Framework for Enhancing Performance Efficiency, Scalability, and Resource Optimization in Data-Intensive Computational Information Systems - Aisyah Revallina; Ambar Sulistyah; Khanien Salsabilla; Alif Ardha; M Razan Wijaya; Padli Arya Wijaya (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2026)
The continuous expansion of data-intensive computational information systems has intensified the demand for high performance efficiency, scalability, and optimal resource utilization, while traditional heuristic-based optimization methods often lack analytical rigor and consistency when applied to increasingly complex and dynamic computational environments. This study proposes a systematic calculus-based analytical framework to enhance performance efficiency by utilizing derivatives and integrals as fundamental tools for modeling system behavior, analyzing performance dynamics, and identifying optimal operational conditions. Through an extensive and structured review of authoritative books and peer-reviewed scientific literature, the study examines how calculus-based methods enable precise evaluation of performance sensitivity, rates of change, and cumulative resource consumption over time. The findings indicate that calculus-based optimization significantly improves key performance indicators, including response time, throughput, scalability, and resource efficiency, particularly in modern computing contexts such as cloud computing, distributed systems, big data platforms, and machine learning applications. Furthermore, gradient-based techniques grounded in calculus are shown to enhance computational efficiency, system adaptability, and predictive accuracy in intelligent information systems. Overall, this study demonstrates that integrating calculus-based analytical approaches provides a rigorous and systematic foundation for performance optimization, supports the development of efficient and scalable computational information systems, and offers a strong theoretical basis for future research on hybrid optimization frameworks that combine mathematical modeling with emerging computational paradigms.